Financial development and economic growth in Malaysia : the stock market perspective - Chee, Keong Choong; Zulkornain, Yusop; Siong, Hook Law; Liew, Venus Khim Sen (Munich Personal RePEc Archive, 2005)
Understanding the causal relationship between financial development and economic growth is important in enhancing the economy of a nation. Using the autoregressive distributed lag (ARDL) bounds test approach, this study finds that stock market development is cointegrated with economic growth in the context of Malaysia. Moreover, this test also suggests that stock market development has a significant positive long-run impact on economic growth. Granger-causality test based on vector error correction model (VECM) further reveals that stock market development Granger-causes economic growth. Hence, this study provides robust empirical evidence in favor of finance-led growth hypothesis for the Malaysian economy.